Altered cerebral perfusion in Parkinson's disease patients with anxiety: an arterial spin labeling MRI study - Li, Lu; Song, Shiyuan; Hu, Yingying; Luo, Yuan; Wang, Lu; Zhang, Peiyao (Frontiers in Neurology, 2025)
PurposeIn this study, we used arterial spin labeling (ASL) to explore altered cerebral blood flow perfusion in Parkinson's disease (PD) patients with anxiety and assessed the relationship between anxiety and perfusion in various brain regions to determine the pathophysiologic basis for the occurrence of anxiety in patients with PD.Materials and methodsSeventy-three patients with PD who were treated at China-Japan Friendship Hospital from September 2023 to November 2024 were enrolled: 36 PD patients with anxiety (PD-A) and 37 PD patients without anxiety (PD-NA); in addition, 37 healthy volunteers were recruited as healthy controls (HCs). All the subjects underwent three-dimensional T1-weighted imaging (3D-T1WI) and pseudo-continuous arterial spin labeling (pCASL) sequential scans via 3.0-T MRI, and cerebral blood flow (CBF) values were obtained from the whole brain. Independent samples t tests and non-parametric Mann–Whitney U tests were applied to test the differences in the CBF values of each brain region between the PD and HC groups, and between the PD-A and PD-NA groups. The relationships between CBF values and anxiety scores in the PD group were also investigated.ResultsCBF values in the bilateral frontal lobes, parietal lobes, temporal lobes, occipital lobes, substantia nigra, striatum, caudate nuclei, left pallidum, and bilateral cerebellum were lower in the PD group than in the HC group (P < 0.05). Compared with those in the PD-NA group, the CBF values of the bilateral frontal lobes, temporal lobes, left putamen and left pallidum were lower in the PD-A group (P < 0.05). CBF values in the left frontal lobe (r = −0.265, P = 0.024), right frontal lobe (r = −0.283, P = 0.015), left temporal lobe (r = −0.287, P = 0.014), and right temporal lobe (r = −0.275, P = 0.019) were negatively correlated with Hamilton Anxiety Scale (HAMA) scores in PD patients.ConclusionThe development of PD-A may be associated with dysfunctional brain perfusion in multiple brain regions, notably the bilateral frontal lobes, temporal lobes, left putamen, and left pallidum. Abnormal CBF in these brain regions may serve as a neuroimaging marker for early PD-A diagnosis. Using ASL to identify perfusion changes in core regions may advance our understanding of the pathophysiological mechanisms underlying PD-A.